Comparative Analysis of the Crime of Overspel (Adultery) in the Articles of the New Criminal Code and the Old Criminal Code Related to Adultery - Wahyumah, Ida; Saputra, Trias (Journal of Social Science, 2024)
Law in Indonesia is still largely influenced by Dutch law, both in terms of legal logic, legal concepts and theories. One of them is the regulation of the crime of adultery which is regulated by Article 284 of the Criminal Code. This setting is considered no longer relevant so it must be updated. The Criminal Code has reformed articles that are no longer in accordance with Indonesian culture. one of which is Article 411 concerning adultery which has been adapted to the norms and culture that apply in Indonesia. The problem taken from this research is a comparative analysis of the crime of overspel (adultery) in the articles of the new criminal code and the old criminal code related to adultery. The research method used in this research is Normative Juridical with the approach used being a statutory approach by analyzing the provisions contained in Articles 284 of the Criminal Code and 411 of the Criminal Code, research sources namely by law, secondary legal sources with scientific articles and books, tertiary book materials with dictionaries. The method of collecting legal materials with reference sources related to research, and the method of analyzing legal materials by understanding and reviewing the data collected. The results of the research concluded that the aim of updating the adultery article in the Criminal Code includes a value reorientation that attempts to accommodate the Indonesian value system in the offenses of adultery and cohabitation in the Criminal Code whose philosophy is in the form of safeguarding and respecting the institution/institutions of marriage, lineage, and upholding the values of marriage. moral values contained in Indonesian society. The aim of this research is to find out the comparison of the adultery article in article 284 of the old Criminal Code. and article 411 of the new Criminal Code. The changes to the adultery article in the Criminal Code are in accordance with the culture and norms that apply in Indonesia.